Mental health of Health Care Workers (HCWs): a review of organizational interventions put in place by local institutions to cope with new psychosocial challenges resulting from COVID-19. (May 2021) - Buselli, Rodolfo; Corsi, Martina; Veltri, Antonello; Baldanzi, Sigrid; Chiumiento, Martina; Lupo, Elena Del; Marino, Riccardo; Necciari, Gabriele; Caldi, Fabrizio; Foddis, Rudy; Guglielmi, Giovanni; Cristaudo, Alfonso
Highlights: COVID-19 pandemic has been associated with significant occupational stressors for healthcare workers (HCWs) Supporting mental health of HCWs is a crucial part of the public health response to the COVID-19 pandemic Many health organizations have already committed resources to the well-being of HCWs, but only a few published their protocols of intervention. Further research is crucial to find out the best ways to support the resilience and mental well-being of HCWs. Abstract: The COVID-19 outbreak has been associated with significant occupational stressors and challenges for healthcare workers (HCWs) including the risk of exposure to SARS-CoV-2. Many reports from all over the world have already found that HCWs have significant levels of self-reported anxiety, depression and even symptoms of post-traumatic stress disorder. Therefore, supporting mental health of HCWs is a crucial part of the public health response to the COVID-19 pandemic. The aim of the present review is to ascertain the interventions put in place worldwide in reducing stress in HCWs during the COVID-19 outbreak. We evidenced how only few countries have published specific psychological support intervention protocols for HCWs. All programs were developed in university associated hospitals and highlighted the importance of multidisciplinary collaboration. All of them had as their purpose to manage the psychosocial challenges to HCW's during the pandemic in order to prevent mental health problems.Whether one program offers distinct benefit compared to the others cannot be known given the heterogeneity of the protocols and the lack of a rigorous protocol and clinical outcomes. Further research is crucial to find out the best ways to support the resilience and mental well-being of HCWs.